P178 Lupus nephritis was associated with low bone mineral density irrespective of duration on steroid treatment in a large UK study of juvenile systemic lupus erythematosus. (23rd March 2020) - Madenidou, Anastasia-Vasiliki; Mahfouz, Yasmin; Chang, Oliver; El-Sharnouby, Farah; Foley, Charlene; Ciurtin, Coziana
Abstract : Background: Estimated 10–20% of all patients with systemic lupus erythematosus (SLE) develop clinical disease before the age of 18 years and are therefore classified as juvenile-onset SLE (JSLE). JSLE patients have a higher prevalence of lupus nephritis (LN) compared to adult-onset SLE 1 and decreased long-term survival compared to JSLE patients without LN. 2 We aimed to identify clinical and laboratory predictors of LN in JSLE patients by comparing the baseline characteristics of JSLE patients with and without LN. Methods: This is a single-center retrospective study, who included JSLE patients reviewed in our young adult and adolescent clinics after transitioning from paediatric services. All data have been analyzed descriptively. Mann- Whitney U or Chi- square test were performed to compare the characteristics between the patients with and without LN. In addition, we performed uni and multivariate analysis to investigate potential predictor biomarkers for LN. Results: We identified 134 JSLE patients, out of which 45 (34%) had LN. The baseline characteristics are detailed in table 1 . As expected, the highest dsDNA levels ever were found in patients with LN (p=0.022). Patients with LN also had longer disease duration (p=0.012). The overall clinical manifestations and complications did not differ between JSLE patients with or without LN, except for the prevalence of low bone mineral density (table 2 ). Factors associated with low bone mineral density in a univariate logistic regression analysis were: the use of mycophenolate mofetil (p=0.021) and the presence of LN (p=0.007), while LN also associated with low bone density (p= 0.008) in a multivariate analysis. The skin involvement was the most common clinical manifestation in both JSLE patient groups. The treatment was more aggressive in patients with LN, including the use of cyclophosphamide, mycophenolate and rituximab, but there was no difference regarding the length of the steroid treatment (table 3 ) . The majority of the patients (67%) had one flare of nephritis and the number of flares ranged from 2 (13%) to 12 (2.2%) for the rest of the patients in this cohort with disease duration ranging from 8–12 years. The class of nephritis was reported in 34 out of 45 patients, and focal lupus nephritis (class III) was the most common type (44%). There were no statistical significant differences in the baseline characteristics or treatments among the different classes of LN. Conclusion: Low bone mineral density is common in patients with JSLE 3, but this is the first study highlighting the association of low bone density with LN and the lack of association with the total duration of steroid treatment or other clinical manifestations. References: Ambrose N, et al. Differences in disease phenotype and severity in SLE across age groups. Lupus . 2016;25(14):1542–50. Smith EMD, et al. Clinical predictors of active LN development in children- evidence from the UK JSLE Cohort Study. Compeyrot-Lacassagne S, et al. Prevalence and etiology of low bone mineral density in Juvenile Systemic Lupus Erythematosus.